2004
DOI: 10.1111/j.1346-8138.2004.tb00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Punctate Palmoplantar Keratoderma (PPK) (Brauer‐Buschke‐Fischer Syndrome)

Abstract: We describe the first case of a sixty-five-year-old male field worker from India, having lesions of hereditary punctate palmoplantar keratoderma with an autosomally dominant pattern of inheritance. Associations included nail abnormalities in the form of longitudinal ridging, onychorrhexis, onychoschizia, trachyonychia and notching, which has been reported only on one previous occasion. The article also presents a brief review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 11 publications
1
24
0
4
Order By: Relevance
“…We found that trachyonychia and twenty-nail dystrophy have been misdiagnosed in the literature in several cases [5,35,41,48,49,50,51,52](table 1). The diagnosis is often incorrectly based on the presence of dystrophic nail changes on all twenty nails, despite the fact that the nails do not show specific signs of trachyonychia.…”
Section: Resultsmentioning
confidence: 99%
“…We found that trachyonychia and twenty-nail dystrophy have been misdiagnosed in the literature in several cases [5,35,41,48,49,50,51,52](table 1). The diagnosis is often incorrectly based on the presence of dystrophic nail changes on all twenty nails, despite the fact that the nails do not show specific signs of trachyonychia.…”
Section: Resultsmentioning
confidence: 99%
“…[5] Trachyonychia may present as an idiopathic disorder of the nails with no other cutaneous or systemic findings or it can be caused by a variety of other disorders. [2,10,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] It has been reported in association with several diseases such as vitiligo [32] and atopic dermatitis, [31] which are also seen in association with alopecia areata (AA). [10] It is the opinion of the reviewer that these cases most likely represent alopecia areata of the nails.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Alopecia areata [10] Atopic dermatitis [31] Autoimmune hemolytic anemia [18] Bart syndrome [19] Congential cutaneous candidiasis [19] Dyskeratosis congenita (Zinsser-Engman-Cole syndrome) [19] Graft-versus host disease [20] Hereditary punctuate palmoplantar keratoderma (Brauer-Buschke-Fischer syndrome) [19] Hidrotic ectodermal dysplasia (Clouston syndrome) [19] Ichthyosis vulgaris [21] Idiopathic thrombocytopenic purpura [18] Immunoglobulin A deficiency [22] Incontinentia pigmenti [23] Koilonychia [24] Lichen planus [25] Nail-Patella syndrome [19] Onychodysplasia of the index fingers [19] Pachyonychia congenita [19] Pemphigus vulgaris [26] Primary biliary cirrhosis [27] Psoriasis [28] Sarcoidosis [29] Trauma [30] Vitiligo [32] acanthosis, focal parakeratosis, and the accumulation of polymorphonuclear cells along the dorsal nail plate. [2] From a morphological point of view, patients who develop trachyonychia in the setting of psoriasis have more thickening of the nail plate as opposed to the thinning seen in lichen planus.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Клиническая карти-на характеризуется множественными участками ороговения желто-коричневого цвета, расположен-ными симметрично на коже ладоней, подошв и сги-бательной поверхности пальцев. Очаги поражения не сливаются между собой, потоотделение не нару-шено [27,28].…”
Section: клиническая дерматология и венерология 2 2015unclassified